PERAN KEPALA SEKOLAH DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DAN MENJADI ROLE MODEL KARAKTER DISIPLIN BAGI WARGA SEKOLAH - Sulastri Sulastri; Liskayani Liskayani; Suliah Suliah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
Principal leadership is all efforts undertaken and the results that can be achieved by the principal in implementing the school to realize the goal of education effectively and efficiently. Principal strategy in improving student achievement is through its role as follows: 1) Principal as leader 2) Principal as manager 3) Principal as supervisor. 4) Principal as innovator. As it is in the fourth pawn, the principal wants to use character education that is already declining. The School Program Plan serves to provide direction and guidance for school principals in order to better and characterize school goals that fall within one of the normative educational strategies. (improvement, development) with little risk and to reduce future uncertainty. School Program Plans should be owned by each school as a guide in the provision of education, both for the long term, medium, and short. School-based change strategies are divided into three strategies: The strategy of coercive power, the rational empirical strategy, and the normative strategy of education.